2007
DOI: 10.1158/0008-5472.can-07-0141
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Activation Results in Enhanced Cyclooxygenase-2 Expression through p38 Mitogen-Activated Protein Kinase–Dependent Activation of the Sp1/Sp3 Transcription Factors in Human Gliomas

Abstract: Expression of cyclooxygenase-2 (COX-2) has been linked to many cancers and may contribute to malignant phenotypes, including enhanced proliferation, angiogenesis, and resistance to cytotoxic therapies. Malignant gliomas are highly aggressive brain tumors that display many of these characteristics. One prominent molecular abnormality discovered in these astrocytic brain tumors is alteration of epidermal growth factor (EGF) receptor (EGFR) through gene amplification and/or mutation resulting in excessive signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
125
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(132 citation statements)
references
References 46 publications
7
125
0
Order By: Relevance
“…It is also gratifying that we were able to show that not only could PEPD induce Cox-2 but this induction also depended on EGFR activation. Although the detailed mechanism by which PEPD induces Cox-2 remains to be elucidated, Xu and Shu (22) reported that EGFR activation in human glioma cells transcriptionally activated Cox-2 via p38 MAPK and Sp1/Sp3, and Lo et al (32) reported that nuclear EGFR bound together with STAT3 to the Cox-2 gene promoter and stimulated Cox-2 gene transcription in human glioma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also gratifying that we were able to show that not only could PEPD induce Cox-2 but this induction also depended on EGFR activation. Although the detailed mechanism by which PEPD induces Cox-2 remains to be elucidated, Xu and Shu (22) reported that EGFR activation in human glioma cells transcriptionally activated Cox-2 via p38 MAPK and Sp1/Sp3, and Lo et al (32) reported that nuclear EGFR bound together with STAT3 to the Cox-2 gene promoter and stimulated Cox-2 gene transcription in human glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several previous studies have indicated that EGFR activation leads to transcriptional activation of Cox-2 (22)(23)(24). To find out if PEPD could bind to EGFR, cell lysates were prepared from Hepa1c1c7 and RT-4 cells, and each lysate (0.5 mg of protein) was incubated with the recombinant PEPD (20 g of protein) in a 0.5-ml volume and the mixture was then subjected to immunoprecipitation with anti-EGFR or an isotype-matched IgG, followed by Western blotting with anti-His (for detection of the recombinant PEPD).…”
Section: Pepd Induces Cox-2 and It Does So Without Requiring Its Dipmentioning
confidence: 99%
“…In fact, a previous study has reported that there is no correlation between EGFR and COX-2 in clinical lung cancer tumor samples or cell lines (46). The difference in results might lie in the alternation of EGFR-downstream signals such as p38 mitogenactivated protein kinase and Sp1/Sp3 to induce COX-2 expression (47). In clinical trials, dual blockage of EGFR and COX-2 in lung cancer leads to disappointing outcomes, since this is not able to overcome the innate resistance of EGFR tyrosine kinase inhibitor (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…These results show that an early genetic event that is necessary and sufficient for the development of a human tumour directly promotes the build-up of an inflammatory microenvironment 8 . Although these 8,9 and other results 10 connect the activation of protein-tyrosine-kinase-encoding oncogenes to inflammation, the precise roles of the various components of the inflammatory microenvironment in the progression of tumours remain to be defined.…”
mentioning
confidence: 99%